2013
DOI: 10.1523/jneurosci.1146-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Precursor Proteins Interact with the Heterotrimeric G Protein Go in the Control of Neuronal Migration

Abstract: Amyloid precursor protein (APP) belongs to a family of evolutionarily conserved transmembrane glycoproteins that has been proposed to regulate multiple aspects of cell motility in the nervous system. Although APP is best known as the source of ␤-amyloid fragments (A␤) that accumulate in Alzheimer's disease, perturbations affecting normal APP signaling events may also contribute to disease progression. Previous in vitro studies showed that interactions between APP and the heterotrimeric G protein Go␣-regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 99 publications
(88 reference statements)
4
50
0
Order By: Relevance
“…In particular, a targeted mutation in the YENPTY motif located in the intracellular domain of APP and involved in the interaction of APP with other proteins such as FE65 and DAB1 ( Figure 2) abrogates the rescue effect of full-length APP in line with the observation that DAB1 and FE65 (Sabo et al, 2001) are also required for migration. Other intracellular proteins such as disrupted-in-schizophrenia 1 (DISC1) (Young-Pearse et al, 2010) and the heterotrimeric G protein Go (Ramaker et al, 2013) may also interact with APP to regulate neuronal migration. In this regard, migration ordinarily depends on linking interactions with the extracellular matrix to the cytoskeleton and motor proteins.…”
Section: Reviewmentioning
confidence: 99%
“…In particular, a targeted mutation in the YENPTY motif located in the intracellular domain of APP and involved in the interaction of APP with other proteins such as FE65 and DAB1 ( Figure 2) abrogates the rescue effect of full-length APP in line with the observation that DAB1 and FE65 (Sabo et al, 2001) are also required for migration. Other intracellular proteins such as disrupted-in-schizophrenia 1 (DISC1) (Young-Pearse et al, 2010) and the heterotrimeric G protein Go (Ramaker et al, 2013) may also interact with APP to regulate neuronal migration. In this regard, migration ordinarily depends on linking interactions with the extracellular matrix to the cytoskeleton and motor proteins.…”
Section: Reviewmentioning
confidence: 99%
“…Numerous studies have demonstrated that APP can function as a neuronal receptor, capable of binding a variety of candidate ligands and transducing intracellular responses that modulate cell adhesion, neuronal outgrowth, and migration (Osterfield et al, 2008; Nikolaev et al, 2009; Rama et al, 2012; Rice et al, 2013). In support of this model, APP can be detected in the growing processes and focal adhesion complexes of cultured cells, suggesting that APP signaling might regulate the cytoskeletal dynamics required for neuronal outgrowth and migration (Sabo et al, 2003; Wang et al, 2005; Young-Pearse et al, 2007; Ramaker et al, 2013). In particular, members of the APP family can function as unconventional G protein-coupled receptors (Nishimoto et al, 1993; Giambarella et al, 1997; Swanson et al, 2005), transducing responses to local cues via the heterotrimeric G protein Goα to regulate neuronal guidance (Brouillet et al, 1999; Ramaker et al, 2013, 2016).…”
Section: Introductionmentioning
confidence: 91%
“…APP is created in the endoplasmic reticulum, and is transported between the cell membrane and the Golgi apparatus (Zheng et al 2012). Within the neuron, increases in synaptic transmission and oxidative stress promote an increase in endocytosis of APP from the cell membrane into endolysosomes (Matsuda et al 2003; Ramaker et al 2013; Zheng et al 2012). Within the endolysosomes, APP is cleaved by secretases [including alpha (α), beta (β) (aka BACE-1), and gamma (γ)] to create amyloid-beta monomers of various lengths (between 39–43 amino acids) including the 42 amino acid length protein Aβ42 and soluble APP (sAPP) peptide fragments (LaFerla et al 2007).…”
Section: Multiple Amyloid Synthesis and Degradation Pathways Exist Inmentioning
confidence: 99%